(3GdQSGdI GdLGeYIs - (3Ydj Hf CHj Ydj Hf eMeO, CHh GdMSf GdeYQha HSja GdOjf GdGeOjs
(3ChdgG (B:s
(3hMOK HNW CHj QMeg Gddg EYde jG CNj HCfg deG cGfJ QJHI GdGfSGfjI eJhSWg Hjf GdehLhOGJ CYfi ef GdedGFcI PcQ GdTjN CHh GdMSjf Cf HbQGW GdMcje hcGf ef LRjQI jhfGf s
(3BNQgG (B:s
(3hhbafGc Ydi eG QSfeGg aGYed YedkG jSJQc Cf JQGg hEf Edi QHc GdefJgi hgPG GdPi CYWi JeJ GdQSGdI GdLGeYI s
(3YHGQI Yf ChQGb ef ChdgG hef BNQgGs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3cJHNGfI edi edc (B(1280) s
Keywords: (3GdadSaI hGdefWbs